Effect of better control of hypertension on left ventricular mass in long term renal transplant recipients - (:unkn) unknown (My University, 2003)
Objective: Control of hypertension (HT) can lead to regression of left ventricular mass index (LVMI) especially in the first year of renal transplantation. However, effect of better control of blood pressure (BP) on regression of LVMI in long-term renal transplant recipients is not known. In this study, we aimed to determine whether improved control of HT would decrease LVMI in renal transplant recipients or not. Methods: Twenty-four nondiabetic renal transplant recipients were included in the final analysis. Patients were categorized into group A (controlled-HT) and group B (uncontrolled-HT) according to their daytime blood pressure levels at the beginning of the study. Antihypertensive drug treatment of patients in group B was modified according to ambulatory blood pressure monitorization (ABPM) and clinical measurements. Echocardiographic examination was performed at baseline and at the end of 24 month. Results: Systolic blood pressure (SBP) and diastolic blood pressure (DBP) declined significantly (p<0.01) in parallel to increased use of angiotensin converting enzyme inhibitor (p<0.01) and LVMI remained unchanged in group B (113 ± 34 g/m2 vs 112 ± 29 g/m2 at baseline and at the end of 24 month, respectively). Although SBP and DBP did not change significantly in group A, LVMI increased significantly (90 ± 21 g/m 2 to 107 ± 26 g/m2 at baseline and at the end of 24 month, respectively) in parallel to increase in serum creatinine (p<0.05) and decline in hemoglobin levels. Conclusions: Our results suggest that control of BP is not sufficient either for the regression or maintenance of LVMI in long term renal transplant recipients. However, factors such as low hemoglobin level and worsening of renal function may play critical roles in the progression of LVMI even in patients with well-controlled BP.
Keywords: Ambulatory blood pressure monitoring; Hypertension; Left ventricular hypertrophy; Renal transplantation